2.0 Academic Management: "Disruptive Innovation" for the 21st Century - Don Chu (Academic Chairpersons Conference Proceedings, 2018)
This workshop will focus on assisting educational leaders to re-imagine academic departments and how they are managed in the 21st Century. Re-imagining academic departments will strengthen them as the foundation upon which college and university change can be built. Led by the chair and the faculty-administrative leadership team, departments will be primarily responsible to set and reach their goals, as well as manage their own resources and professional development. Themes that will be discussed include curriculum development, course schedules, students services, personnel and ‘political’ issues, departmental resources, and more.
Keywords: Academic Management Disruptive Innovation 21st Century